Collective Intelligence and Structural Transformation in the Moroccan Tourism Industry during the COVID-19 Pandemic: A Field Survey in the Marrakech-Safi Region - MERIOUMI, Wijdane; AIBOUD BENCHEKROUN, Bouchra (Journal of Environmental Management and Tourism, 2023)
This paper discusses the impact of the COVID-19 pandemic on the tourism industry, with a focus on the Moroccan tourism sector. It highlights the need for the government to reflect on the crisis's implications and foster a more resilient tourism economy through structural transformation and collective intelligence. This research defines key concepts of collective intelligence and analyzes the mechanisms of actors in the Moroccan tourism sector. The study conducted a field survey in the Marrakech-Safi region, showing that market actors have developed effective tools and methods of collective action in line with collective intelligence principles. By promoting collective intelligence, Morocco can create a sustainable and resilient tourism industry. The study's contributions can provide valuable information for similar contexts worldwide, and its findings are of interest to researchers, policymakers, and practitioners in the tourism industry.